The Application of Guided Inquiry to Students' Critical Thinking Skills in Pancasila Education Subjects with Self-Efficacy as a Moderator Variable - Mawaddah, Sharihatul; Syahri, Mohamad; Soenaryo, Siti Fatimah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study examines the effect of the Guided Inquiry learning model on senior high school students’ critical thinking skills in Civic Education, with academic self-efficacy tested as a moderating variable. This study examines the effect of the Guided Inquiry learning model on students’ critical thinking skills in Civic Education and investigates the moderating role of academic self-efficacy. The population comprised all eleventh-grade students at Muhammadiyah 02 Islamic High School, Lamongan, in East Java. Samples were selected using cluster random sampling, resulting in 79 students divided into an experimental group (n = 40) and a control group (n = 39). A quasi-experimental 2×2 factorial design was employed. Data were collected using validated and reliable test instruments and analyzed using two-way ANOVA. The results show that the Guided Inquiry model significantly improves critical thinking skills compared to conventional instruction (p < .05). Academic self-efficacy also has a significant main effect (p < .05) and interacts with the learning model (p < .05). These findings indicate that Guided Inquiry is effective for enhancing critical thinking, particularly among students with higher self-efficacy. Data were collected through validated instruments consisting of a critical thinking skills test and a self-efficacy questionnaire. Statistical analyses, including Two-Way ANOVA, were conducted to examine main effects and interaction effects. Findings indicate that (1) the Guided Inquiry model significantly improved students’ critical thinking skills compared to conventional instruction; (2) students with high self-efficacy outperformed those with low self-efficacy; and (3) a significant interaction occurred between learning model and self-efficacy.